2002
DOI: 10.1143/jjap.41.2353
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Understanding of Electron and Hole Mobility Limited by Surface Roughness Scattering in Pure Oxides and Oxynitrides Based on Correlation Function of Surface Roughness

Abstract: A new model of the roughness correlation function S(r) has been proposed in order to explain the different behavior of high field mobility limited by surface roughness scattering, µ SR , between electrons and holes in metal oxide semiconductor field effect transistors (MOSFETs) with oxynitrides. It has been shown, for the first time, that the change in electron and hole µ SR associated with NO oxynitridation can be reasonably well explained by the appropriate choice of the form of S(r).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…SRS limited mobility (μ SRS ) is extracted by line fit to μ-Ns curve at high Ns region and expressed by following expression, μ SRS = αxNs β . Changes of α and β mainly correspond to changes of amplitude and distribution of roughness (or surface potential fluctuation), respectively [10,14,15] . Figure 10 shows Δμ SRS as a function of Ns.…”
Section: T Shift and Mobility Degradationmentioning
confidence: 99%
“…SRS limited mobility (μ SRS ) is extracted by line fit to μ-Ns curve at high Ns region and expressed by following expression, μ SRS = αxNs β . Changes of α and β mainly correspond to changes of amplitude and distribution of roughness (or surface potential fluctuation), respectively [10,14,15] . Figure 10 shows Δμ SRS as a function of Ns.…”
Section: T Shift and Mobility Degradationmentioning
confidence: 99%
“…13 In order to describe the mobility of both electrons and holes, alternative expressions have been proposed both in real and reciprocal space. 14,15 These alternative expressions include an additional exponential parameter n, which for specific values reduce to the Gaussian and exponential models. No physical meaning has been given to this exponential parameter.…”
Section: Introductionmentioning
confidence: 99%
“…No physical meaning has been given to this exponential parameter. Isihara et al 14 studied the silicon interface with pure silicon dioxide (SiO 2 ) and with oxynitrides (SiON x ). They found that different values of the exponential parameter n were needed to successfully describe the roughness of both interfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The N sub are 2x10 17 , 7x10 17 , and 2x10 18 cm -3 . In high-E eff region, μ of SiON is higher than SiO 2 universal μ due to modulation of surface roughness scattering (SRS) by nitrogen [13] . μ of high-k MISFETs degrades as compared to the SiO 2 MISFET (except for very high-E eff region) due to high-k inherent scattering such as remote Coulomb scattering (RCS) or remote phonon scattering [14] .…”
mentioning
confidence: 99%